Implementation of the Calistung Guidance Program as an Effort to Strengthen Literacy and Numeracy Of Elementary School Children At The Muhammad Fahri Integrated MIS, Dusun Ii, Sauh Village, Tembung - Nur Wahyuni; Audisa Salsabila; Hepi Dwi Januwariska; Rosmita Hasibuan; Winda Santika Harahap; Yahayu; Suhandiro Wibowo (Outline Publisher, 2026)
This research is motivated by the phenomenon of low literacy skills (reading and writing) and numeracy (calculation) of elementary school children in Hamlet II, Sauh Village, Tembung, this is seen from the lack of basic reading and arithmetic skills. This study aims to implement a Calisrung (Read, Write, Calculate) mentoring program for elementary school children in Hamlet II, Sauh Village, Tembung. The methods used are the preparation stage (observation and problem identification), implementation, and evaluation. The results show that there is an increase in students' interest in learning and basic abilities in arithmetic and reading after the implementation of this program. Thus, the Calistung mentoring program is effective as an effort to strengthen early literacy and numeracy for elementary school children.